Anesthetic Approach In A Patient With A Left Submandibular Colli Abscess and Multiple Comorbidities - Richard, Richard; Mas Shintya Dewi, Dewa Ayu; Gede Widnyana, I Made (Syntax Corporation, 2025)
Submandibular–colli abscess accompanied by comorbidities such as diabetic ketoacidosis (DKA), airway obstruction, and chronic heart failure (CHF) presents a complex anesthetic challenge. Patients with maxillofacial abscesses and comorbidities such as impending airway obstruction, diabetic ketoacidosis (DKA), and chronic heart failure pose significant challenges to anesthetic management. Each comorbidity significantly influences perioperative management and increases the risk of morbidity and mortality. The goal of preoperative management is to stabilize the patient prior to surgery and reduce the risk of perioperative complications. Preoperative management includes ensuring adequate oxygenation, optimizing and monitoring hydration status, and controlling blood glucose levels. Objectives: To describe the perioperative anesthetic approach in a patient with a left submandibular abscess and multiple comorbidities, emphasizing the importance of a holistic strategy in managing complex surgical cases. Case Report: A 51-year-old female presented with progressive swelling of the left face and neck for two weeks. Examination revealed a submandibular abscess, DKA, and a known history of CHF. The patient reported trismus and odynophagia with marked hyperglycemia. Imaging showed tracheal deviation and abscess extension to the retropharyngeal space. Preoperative management focused on metabolic stabilization and cardiovascular optimization. Awake fiberoptic intubation (AFOI) with dexmedetomidine sedation was performed due to the anticipated difficult airway. Surgery proceeded uneventfully for 2 hours and 10 minutes, followed by intensive postoperative monitoring. Discussion: Anesthetic management in patients with deep neck abscesses and comorbid DKA and CHF requires comprehensive perioperative planning. Metabolic and hemodynamic stability must be achieved prior to induction. Careful airway planning, the use of cardiovascularly stable anesthetic agents, and vigilant glucose and fluid monitoring are essential to prevent complications. Conclusion: Successful anesthetic care in patients with submandibular abscess and complex comorbidities demands coordinated, individualized perioperative strategies to minimize risk and optimize outcomes.